Entrepreneurial behaviour : unveiling the cognitive and emotional aspects of entrepreneurship - Caputo, Andrea; Pellegrini, Massimiliano M. (Emerald Publishing Limited, 2020)
The success, longevity, and survival of SMEs are deeply linked to the effectiveness of individual decision-making processes, and established firms need to develop an entrepreneurial and innovative decision-making processes to maintain competitive advantages in a continuously changing and increasingly turbulent environment.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Entrepreneurship -- Psychological aspects; Business & Economics -- Entrepreneurship; Entrepreneurship